1985
DOI: 10.1002/ajmg.1320220412
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variation in the del(12p) syndrome

Abstract: Previous reports suggested the existence of a del(12p) syndrome. Phenotypic abnormalities associated with del(12p) appear to be mental retardation, microcephaly, and micrognathia. The patient with del(12p) reported here was normocephalic and large for gestational age. She probably had sclerocornea, a finding not previously associated with del(12p). Phenotypic variation in del(12p) syndrome is probably caused by differences in the size of the deleted segment and/or the presence or absence of mutant genes on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…Major characteristics of the phenotype of trisomy 12p, Pallister-killian syndrome, include severe psychomotor retardation, generalized hypotonia, round face with prominent cheeks, flat and broad nasal bridge with short nose (32). In addition, deletion of this region has been associated with severe psychomotor retardation and facial dysmorphism (33). Although the phenotypes may be attributed to more than one gene, DEC2 is considered to be an attractive candidate gene for the disease, because the bHLH transcription factor is essential for normal tissue development.…”
Section: Decs Form a Subfamily Within Bhlh Proteinsmentioning
confidence: 99%
“…Major characteristics of the phenotype of trisomy 12p, Pallister-killian syndrome, include severe psychomotor retardation, generalized hypotonia, round face with prominent cheeks, flat and broad nasal bridge with short nose (32). In addition, deletion of this region has been associated with severe psychomotor retardation and facial dysmorphism (33). Although the phenotypes may be attributed to more than one gene, DEC2 is considered to be an attractive candidate gene for the disease, because the bHLH transcription factor is essential for normal tissue development.…”
Section: Decs Form a Subfamily Within Bhlh Proteinsmentioning
confidence: 99%
“…Seven major structural anomalies were noted in 3 patients. Each of them involved different organ systems: hypoplastic right lung, absent right pulmonary artery, and atrial septa1 defect were present in the child described by Mayeda et al, [1974]; bilateral choanal atresia, several skeletal anomalies, agenesis of the corpus callosum, and omphalocele were found in the case of Kivlin et al, [1985] and unilateral cleft lip in the present stillborn infant.…”
Section: Discussionmentioning
confidence: 87%
“…Deletions involving the short arm of chromosome 12 are rare: to the best of our knowledge only 10 patients have been reported to date with a del(l2p) as an isolated chromosome aberration. Six of these subjects have proximal interstitial deletions of 5 different segments [Malpuech et al, 1975;Tenconi et al, 1975;Orye and Craen, 1975;Magenis et al, 1981;Boilly-Dartigalongue et al, 19851, while the remaining 4 have distal deletions of varying length [Mayeda et al, 1974;Magnelli and Therman, 1975;Kivlin et al, 1985;Romain et al, 19871. Furthermore, 3 subjects have a terminal deletion of 12p with additional chromosome aberrations [Juberg et al, 1984;Orye et al, 1985;Rivas et al, 19851, and there are 5 reported cases of ring chromosome 12 [Hamerton et al, 1973;Scribanu et al, 1980;Zuffardi et al, 1980;Park et al, 19881. We report on a stillborn female with a deletion of the terminal band 1 2~1 3 and review the clinical data of the reported cases of distal del(l2p) to contribute to the delineation of the phenotype associated with this chromosome abnormality.…”
Section: Introductionmentioning
confidence: 99%
“…Although Magnelli and Therman [1975] proposed a ''12p deletion syndrome'', identical or comparable well characterized cases in the literature are rare [Stumm et al, 2007]. Although, the severity of the anomalies seen in these cases does not appear to correlate with the size of the deletion, it has been suggested that the variation in the clinical features seen in patients with del(12p) may be explained by the different sizes and locations in 12p of the deleted segments [Kivlin et al, 1985]. It is tempting to speculate that another genetic aspect may be implicated, such as imprinting or copy number variation [MacDonald et al, 2010].…”
Section: Discussionmentioning
confidence: 94%